Evaluation of the effect of an offset implant configuration in the posterior maxilla with external hexagon implant platform: A 3-dimensional finite element analysis - Souza Batista, Victor Eduardo de [UNESP]; Verri, Fellippo Ramos [UNESP]; Faria Almeida, Daniel Augusto de; Santiago Junior, Joel Ferreira; Araujo Lemos, Cleidiel Aparecido [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Elsevier B.V., 2017)
Statement of problem. Slight offset of the central implant in 3-unit implant-supported prostheses has been reported to improve biomechanical behavior. However, studies that assessed the effects of an offset implant configuration in the posterior maxilla are scarce. Purpose. The purpose of this 3-dimensional (3D) finite element analysis was to assess the effects of splinting in 3-unit implant-supported prostheses with varying implant positions (straight-line or offset configuration) in terms of the stress/strain distribution on bone tissue and the stress distribution on abutment screws. Material and methods. Three 3D models were used to simulate a posterior maxilla bone block (type IV): straight-line implants supporting single crowns (model M1), straight-line implants supporting 3 -unit splinted fixed dental prosthesis (model M2), and an offset implant configuration supporting 3 -unit splinted fixed dental prosthesis (model M3). The applied forces were 400 N axially and 200 N obliquely. The type of implant platform simulated was an external hexagon. von Mises stress on the abutment screws was measured, and the maximum principal stress and microstrain values were used to perform cortical bone tissue analysis. Analysis of variance (ANOVA) and the Tukey honest significant differences post hoc test were used to determine the significance of the results and interactions among the main variables (alpha=.05). Results. In all models, oblique load increased the stress on abutment screws and bone tissue and the microstrain on bone tissue. Model M3 decreased the stress concentration on the abutment screws and bone tissue. With regard to microstrain distribution, model M3 had the smallest values, and M1 and M2 had similar values. Conclusions. Splinting associated with an offset implant configuration was effective for decreasing the stress on abutment screws and bone tissue and the microstrain on bone tissue.